Residual Stroke Risk Among Patients With Atrial Fibrillation Prescribed Oral Anticoagulants: A Patient‐Level Meta‐Analysis From COMBINE AF - Linda S. Johnson; Alexander P. Benz; Ashkan Shoamanesh; John W. Eikelboom; Michael Ezekowitz; Robert P. Giugliano; Lars Wallentin; Christian T. Ruff; Renato D. Lopes; Sanjit Jolly; Richard Whitlock; Christopher B. Granger; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Despite oral anticoagulation, patients with atrial fibrillation (AF) remain at risk of ischemic stroke and systemic embolism (SE) events. For patients whose residual risk is sufficiently high, additional therapies might be useful to mitigate stroke risk. Methods and Results Individual patient data from 5 landmark trials testing oral anticoagulation in AF were pooled in A Collaboration Between Multiple Institutions to Better Investigate Non‐Vitamin K Antagonist Oral Anticoagulant Use in AF (COMBINE AF). We calculated the rate of ischemic stroke/SE among oral anticoagulation–treated patients with a CHA2DS2‐VASc score≥2, across strata of CHA2DS2‐VASc score, stroke history, and AF type, as either paroxysmal or nonparoxysmal. We included 71 794 patients with AF (median age 72 years, interquartile range, 13 years, 61.3% male) randomized to a direct oral anticoagulant or vitamin K antagonist, and followed for a mean of 2.1 (±0.8) years. The median CHA2DS2‐VASc score was 4 (interquartile range, 3–5), 18.8% had a prior stroke, and 76.4% had nonparoxysmal AF. The overall rate of stroke/SE was 1.33%/y (95% CI, 1.27–1.39); 1.38%/y (95% CI, 1.31–1.45) for nonparoxysmal AF, and 1.15%/y (95% CI, 1.05–1.27) for paroxysmal AF. The rate of ischemic stroke/SE increased by a rate ratio of 1.36 (95% CI, 1.32–1.41) per 1‐point increase in CHA2DS2‐VASc, reaching 1.67%/y (95% CI, 1.59–1.75) ≥4 CHA2DS2‐VASc points. Patients with both nonparoxysmal AF and CHA2DS2‐VASc ≥4 had a stroke/SE rate of 1.75%/y (95% CI, 1.66–1.85). In patients with a prior stroke, the risk was 2.51%/y (95% CI, 2.33–2.71). Conclusions AF type, CHA2DS2‐VASc score, and stroke history can identify patients with AF, who despite oral anticoagulation have a residual stroke/SE risk of 1.5% to 2.5% per year. Evaluation of additional stroke/SE prevention strategies in high‐risk patients is warranted.